Public Health Implications for Flood Control Based on Drainage Technology for Retention Ponds, Infiltration Wells, and Water Pumps in Indonesia : a Review - Dewi Sartika; Agista Agista; Fifiani; Fitriana (Journal of Epidemiology and Health Science, 2026)
Background: Flooding is one of the most common natural disasters in urban areas, driven by heavy rainfall, climate change, poor water resource management, rapid urbanization, land-use change, and deforestation. Effective drainage infrastructure, including retention ponds, infiltration wells, and water pumps, plays a critical role in reducing flood risks and protecting public health. Objective: This study aimed to analyze and evaluate the effectiveness of drainage technologies, namely retention ponds, infiltration wells, and water pumps, in urban flood control from a public health perspective. Methods: A literature review was conducted using articles retrieved from PubMed and Google Scholar. Relevant studies were identified using keywords related to drainage technology, retention ponds, infiltration wells, and water pumps. Selected articles were analyzed to assess their contributions to flood mitigation and community health outcomes. Results: The findings indicate that urban flooding in Indonesia is influenced by both natural and anthropogenic factors, including high rainfall, inadequate waste management, and land-use changes. Drainage technologies have been shown to reduce flood volume, enhance groundwater recharge, and improve environmental quality. Major challenges include limited drainage capacity, low public awareness, and rapid urban expansion. Improved drainage systems also contribute to public health by reducing stagnant water, thereby lowering the risk of mosquito-borne and water-related diseases. Conclusion: Retention ponds, infiltration wells, and water pumps are effective flood-control measures that support environmental sustainability, groundwater conservation, and public health improvement in urban areas. Keywords: flood control, environmentally sound drainage, retention ponds, infiltration wells, water pumps, groundwater conservation